AN INVESTIGATION OF THE YENİ HESÂB (NEW CALCULUS) AND YENİ HENDESE (NEW GEOMETRY) TEXTBOOKS OF KİRKOR KÖMÜRCİYAN, ONE OF THE LATEST OTTOMAN MATHEMATICIANS, IN THE CONTEXT OF ASSOCIATION SKILLS - Çay, Tuğba; İncikabı, Lutfi; Takıcak, Müjdat (Kastamonu Egitim Dergisi, 2025)
In this study the transliteration of two books named Yeni Hesâb and Yeni Hendese, written by Kirkor Kömürciyan, one of the successful late Ottoman mathematicians, was made by the researcher with expert support and the association skills in the book content were examined. The data of the study was created by document analysis, one of the qualitative research methods. While examining mathematical association skills, four main headings within the concept framework created by Bingölbali and Coşkun (2016) were used. Each activity in the textbooks are categorized and divided into classes by a mathematics expert within the framework of these four main headings. After all classification processes, frequency tables of the activities were created, and the findings were prepared. As a result of the study, findings regarding the ability to make positive associations were found in both books Yeni Hesâb and Yeni Hendese, although they were written in 1925. In the context of different representations, it was found that the most relationships were seen in both books, and the interdisciplinary relationships were the least. While the most relationship was seen between different representations of the concept, it was found that the relationship between disciplines was the least. Associations with real life have been used to a considerable extent both in examples and exercises, as well as in lectures and activities.